Archaeological sites in the area of Ražanac, Podvršje and Ljubač in function of valorisation of cultural and sport tourism - Miočić, Josip; Vukašina, Martina (Oeconomica Jadertina, 2020)
The paper provides an overview of the most important archaeological sites in the wider area of Ražanac, Podvršje and Ljubač, which date from prehistory to New Age. Since a significant part of the explored sites are located on natural hills, sea bays and water-rich areas, their role as a kind of catalyst in the promotion of cultural and natural beauty of the area is highlighted. In this context, localities have become important destinations in the development of cultural and sports tourism, as a unified form of the local community tourist offer. The position of Ljubljana above Ljubač (Castrum Liube) as a complex archaeological site that offers a layered historical story is especially noteworthy. Due to its natural environment, the mentioned position above Ljubač is ideal for setting up cultural and sports-recreational trails, and ultimately the area has excellent predispositions for the formation of an archaeological park in the future. Such a thing would certainly affect local economic growth and development. This is especially pronounced on the economic impact of the organization of cultural and sporting events.